Deciphering financial statements in annual reports - SUWARDY, Themin (Institutional Knowledge at Singapore Management University, 2019)
In the first of a three-part weekly series on financial literacy, SMU Dean of Postgraduate Professional Programmes and Associate Professor of Accounting (Practice) Themin Suwardy, SIT’s Professor Ho Yew Kee and Associate Professor Edmund Keong from NUS discussed the importance of learning to read and analyse financial statements. They opined that being able to decipher financial statements is critical if an investor wants to have a real understanding of a company's profitability, liquidity and cash position. This will equip them with useful information to make informed decisions.